"Acreanidade": invenção e reinvenção da identidade acreana - Morais, Maria de Jesus (2008)
This thesis focuses on the construction of a certain Acrean identity set in motion by the Forest Government (self denomination of the state government), in 1999. The Acrean identity subsumed under the term acreanidade is discussed here under the perspective of the Geography concept of territoriality. Territorial identities are those which are constructed having as references the spaces of identity references , i.e. the territory. The concept of acreanidade is looked into under two dimensions: historical and geographical. The historic dimension is anchored on a collective memory, which is also constructed under the guidance of the government official historian, by connecting three historical events (Acre Revolution, Autonomist Movement, Indians and rubber tappers Social Movement). The geographical dimension is anchored on the spaces of identity reference which are also obviously constructed or selected. Throughout the text there are highlighted the discursive processes that invent and re-invent the state of Acre and the Acrean inhabitants, that is to say, the discourses which are founders and re-founders of the proclaimed acreanidade. Attention is also given to the creation of spaces for, and in the memory and to the choice of some spaces of identity reference, since those are also part of a territorial discourse. Considering that territorial interventions are themselves discourse in action, material expressions of a certain conception of city, we also discuss the patrimonialization of the capital city Rio Branco and of the two towns Porto Acre and Xapuri which have undergone an intense process of urban revitalization. The Acrean identity is thus analyzed as a construct, open to multiple reconstructions, and malleable to inclusion of events, characters and places which may contribute more efficiently to re-affirm the yet-in-construction identity